Step-by-step explanation:
Answer is attached....of both the parts.
Hope it helps:)
Answer:
![y=-30](https://tex.z-dn.net/?f=y%3D-30)
Step-by-step explanation:
we are given
y varies directly as x
so, we can write equation as
![y=kx](https://tex.z-dn.net/?f=y%3Dkx)
where
k is constant of proportionality
We have
at x=-1 , y=6
so, we can use it to find k
![6=k(-1)](https://tex.z-dn.net/?f=6%3Dk%28-1%29)
so, we get
![k=-6](https://tex.z-dn.net/?f=k%3D-6)
now, we can plug it back
![y=-6x](https://tex.z-dn.net/?f=y%3D-6x)
now, we can plug x=5
and we get
![y=-6\times 5](https://tex.z-dn.net/?f=y%3D-6%5Ctimes%205)
![y=-30](https://tex.z-dn.net/?f=y%3D-30)
1813 x
![\frac{18}{100}](https://tex.z-dn.net/?f=%20%5Cfrac%7B18%7D%7B100%7D%20)
= 326.34
18% of 1813 people is 326.34 people
333 is a reasonable estimate.
Answer:
The answer is 16 I've seen this before so I would know. and your welcome
Step-by-step explanation:
Answer:
![x=\frac{ln7}{2ln5-ln7}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7Bln7%7D%7B2ln5-ln7%7D)
Step-by-step explanation:
5^2x=7^x+1 ⇔ ln5^2x = ln7^x+1 ⇔ 2xln5 = (x+1)ln7 ⇔ (2ln5-ln7)x = ln7
⇔ x = ln7/(2ln5-ln7)